Corporate Governance Role as Moderating Green Intellectual Capital and Green Accounting Influence on Sustainable Finance Implementation in IDX Listed Banks - Riyanti, Yulia Eka; Murwaningsari, Etty (Devotion : Journal of Research and Community Service, 2023)
The sustainable finance implementation is a comprehensive support for the financial services industry as an intermediary institution that supports Sustainable Development Goals. The purpose of this study was to analyze the role of corporate governance mechanisms as moderating effect of green intellectual capital and green accounting on sustainable finance implementation in banks listed on the Indonesia Stock Exchange. The study use quantitative method and data in this study uses 149 firm years banking companies taken from the company's Annual Report and/or Sustainability Report using the 2016 to 2020 observation period. This study uses the Moderated Regression Analysis (MRA) method. The result of study that green human capital, green structural capital and green accounting have a positive effect on sustainable finance implementation. Meanwhile, green relational capital has no effect on sustainable finance implementation. In addition, the corporate governance mechanism is not able to moderate the influence of green human capital, green structural capital, green relational and green accounting on sustainable finance implementation. For control variables, firm size, leverage and firm age have an effect on sustainable finance implementation, while profitability has no effect on sustainable finance implementation.